Multi-objective optimization of a PEMFC based CCHP system by meta-heuristics - Yan Cao; Yujia Wu; Leijie Fu; Kittisak Jermsittiparsert; Navid Razmjooy (Energy Reports, 2019)
This paper presents a multi-criteria economics, environment, and thermodynamics assessment for a combined cooling, heating, and power (CCHP) system consist of a heat recovery system, a small absorption chiller, a 5kW PEMFC stack, gas compressor, and a humidifier. This study presents an improved version of a new optimization technique called improved emperor penguin optimization (IEPO) algorithm for optimizing the system efficiency. After simulations, the system is analyzed in terms of energy and exergy efficiencies, annual cost, and pollutant emission reduction. Simulation results declare low operating temperature develop GHG emission reduction, high relative humidity, pressure of inlet gases, and system exergy performance. The results of the IEPO algorithm are the compared with the standard EPO and also NSGA-II as a widely used optimization algorithm for showing the superiority of the algorithm.
Keywords: 330; Combined cooling; heat and power system; Emperor penguin optimization algorithm; Improved; Multi-criteria assessment; Proton exchange membrane